0532 Cognitive Behavioral Therapy Delivered Via Telemedicine vs. Face-to-Face: Results from a Randomized Controlled Non-Inferiority Trial. (27th May 2020) - Arnedt, J; Conroy, D; Mooney, A; DuBuc, K; Balstad, S; Pace, D; Yang, A; Furgal, A; Sen, A; Eisenberg, D
Abstract: Introduction: Telemedicine is increasingly an option for delivery of healthcare services, but its efficacy and acceptability for delivering CBT for insomnia has not been adequately tested. In a randomized controlled non-inferiority trial, we compared face-to-face and telemedicine delivery (via the AASM SleepTM platform) of CBT for insomnia for improving sleep and daytime functioning at post-treatment and 12-week follow-up. Methods: Sixty-five adults with chronic insomnia (46 women, mean age 47.2 ± 16.3 years) were recruited primarily from insomnia clinics and screened for disqualifying sleep, medical, and mental health disorders. Eligible participants were randomized to 6 sessions of CBT for insomnia delivered face-to-face (n=32) or via AASM SleepTM (n=33). Participants completed self-report measures of insomnia (Insomnia Severity Index, ISI) and daytime functioning (fatigue, depression, anxiety, and overall functioning) at pre-treatment, post-treatment, and 12-week follow-up. The ISI was the primary non-inferiority outcome. Results: Telemedicine was non-inferior to face-to-face delivery of CBT for insomnia, based on a non-inferiority margin of 4 points on the ISI (β = -0.07, 95% CI -2.28 to 2.14). Compared to pre-treatment, ISI scores improved significantly at post-treatment (β = -9.02, 95% CI -10.56 to -7.47) and at 12-week follow-up (β = -9.34, 95% CI -10.89 to -7.79). Similarly, daytime functioning measures improved from pre- to post-treatment, with sustained improvements at 12-week follow-up. Scores on the fatigue scale were lower in the telemedicine group at both post-treatment (F=4.64, df=1, 119, p<.03) and follow-up (F=5.79, df=1, 119, p<.02). Conclusion: Insomnia and daytime functioning improve similarly whether CBT for insomnia is delivered via telemedicine or face-to-face. Telemedicine delivery of CBT for insomnia should be implemented more systematically to improve access to this evidence-based treatment. Support: American Sleep Medicine Foundation Grant # 168-SR-17 (JT Arnedt, PhD)